Construction of effective transmission channels by anchoring metal‐organic framework on side‐chain sulfonated poly(arylene ether ketone sulfone) for fuel cells. (8th April 2022) - Ju, Mengchi; Shi, Qingyuan; Xu, Jingmei; Chen, Xuan; Ren, Jiahui; Lei, Jinxuan; Meng, Lingxin; Zhao, Pengyun; Wang, Zhe
Summary: A series of novel organic‐inorganic hybrid membranes assembled by side‐chain type sulfonated poly(arylene ether ketone sulfone) with amino groups (Am‐SPAEKS‐DBS) and ZIF‐67 were prepared. Am‐SPAEKS‐DBS containing double bonds was synthesized by condensation polymerization, and the AMPS was grafted onto the main chain by post sulfonation. ZIF‐67 was prepared by an ordinary solvent method. The structures of ZIF‐67, Am‐SPAEKS‐DBS, and hybrid membranes were analyzed by proton nuclear magnetic resonance ( 1 H NMR), scanning electron microscopy (SEM), powder X‐ray diffraction (PXRD) and Fourier transform infrared (FT‐IR). All hybrid membranes had good dimensional stability and excellent oxidation stability. In addition, the swelling ratios of all hybrid membranes were low (<17.46%) at even 100°C, and the oxidative stability was higher than 92%. The proton conductivities of this series of membranes were much higher (0.0540.069 S cm −1 at 30°C, 0.088‐0.116 S cm −1 at 80°C) than pure membrane (0.038 S cm −1 at 30°C, 0.076 S cm −1 at 80°C). The experimental results exhibited that the comprehensive properties of hybrid membranes are good, and hybrid membranes had substantially possible as proton exchange membranes. Highlights: Metal‐organic frameworks were anchored on side‐chain type organic polymer backbone. The hybrid PEMs showed good dimensional stability and excellent oxidation stability. The imidazole as a ligand in ZIF‐67 contributes a part of the dissociated protons. Abstract : A series of novel organic‐inorganic hybrid membranes assembled by side‐chain type sulfonated poly (arylene ether ketone sulfone) with amino groups (Am‐SPAEKS‐DBS) and ZIF‐67 were prepared. Structures of ZIF‐67, Am‐SPAEKS‐DBS and hybrid membranes were analyzed by 1 H NMR, SEM, PXRD and FT‐IR. Hybrid membranes had good dimensional stability, oxidation stability (>92%) which swelling ratios were low (<17.46%) at 100 °C, the highest conductivity was 0.116 S cm −1 and peak power density of Am‐S‐D‐AMPS/ZIF‐67‐10% was 283.48 mW cm −2 at 80 °C.